Comparison of financial performance and dividend policy before and after merger - Purwanti Purwanti; Widiastuti Widiastuti (Institute of Computer Science (IOCS), 2024)
The study aims to analyze the impact of the merger on the financial performance and dividend policy of PT Bank Syariah Indonesia Tbk, after making the 2021 merger, compared with financial performance as well as dividend policies before making the merging. The research uses descriptive quantitative research, using secondary data obtained from the official website of the Financial Services Authority (OJK) and also the official web site of PT Bank Syariah Indonesia. The variables used in the study include Return on Assets (ROA), Return On Equity (ROE), Operational Costs to Operational Income (BOPO), Financing to Deposit Ratio (FDR), Non Performing Finance (NPF), and Dividend Payout Ratio. (DPR). The analysis method used to answer hypotheses 1 to 6 uses the normality test of the data, and the differential test uses the Paired Sample T-test. The results obtained from this study showed that during the 2 years before and 2 years after the merger ROA, ROE, BOPO, and NPF had significant differences after it made merger, but for FDR and the DPR, there was no significant difference after 2 years of merger.